2022
DOI: 10.1002/ange.202114437
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐relationships between Oxygen Evolution and Iridium Dissolution Mechanisms

Abstract: Figure 1. a) Electrochemical oxide pathway. [13] Copyright 2016, John Wiley and Sons. b) Cationic redox mechanism proposed by Kçtz et al. [21] Copyright 1984, IOP Publishing. c) Scheme of the OER, including the formation of an OOH intermediate, as detected by Sivasankar et al. [24] Copyright 2011, AmericanC hemical Society.d )Schematic representation of O2pbands penetrating into Ir dorbitals and triggering an anionic redox process. [27] Copyright 2016, Springer Nature. e) OER scheme showing the formation of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 103 publications
(170 reference statements)
0
3
0
Order By: Relevance
“…14 The higher stability was hypothesized to stem from kinetically hindered dissolution 11 and lower participation of lattice oxygen during the OER. 15 A study focusing on the transferability of IrO x dissolution stability from AMSs to single-cell electrolyzers indicated a substantial underestimation of Ir stability in the AMS, mainly attributed to differences in the systems' pH and measurement duration. 16 To quantify IrO x dissolution from catalyst layers in singlecell electrolyzers, so far post-mortem transmission electron microscopy (TEM) analysis of catalyst coated membrane (CCM) cross sections 17,18 and additionally dissolution of the cathode CL and quantification by ICP-MS 19 were utilized, sacrificing the investigated CCM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The higher stability was hypothesized to stem from kinetically hindered dissolution 11 and lower participation of lattice oxygen during the OER. 15 A study focusing on the transferability of IrO x dissolution stability from AMSs to single-cell electrolyzers indicated a substantial underestimation of Ir stability in the AMS, mainly attributed to differences in the systems' pH and measurement duration. 16 To quantify IrO x dissolution from catalyst layers in singlecell electrolyzers, so far post-mortem transmission electron microscopy (TEM) analysis of catalyst coated membrane (CCM) cross sections 17,18 and additionally dissolution of the cathode CL and quantification by ICP-MS 19 were utilized, sacrificing the investigated CCM.…”
Section: Introductionmentioning
confidence: 99%
“…Rutile IrO 2 was shown to be up to 2 orders of magnitude more stable during the OER, compared to hydrous IrO x in an aqueous model system (AMS) . The higher stability was hypothesized to stem from kinetically hindered dissolution and lower participation of lattice oxygen during the OER . A study focusing on the transferability of IrO x dissolution stability from AMSs to single-cell electrolyzers indicated a substantial underestimation of Ir stability in the AMS, mainly attributed to differences in the systems’ pH and measurement duration …”
Section: Introductionmentioning
confidence: 99%
“…The stability is another challenge possibly caused by the dissolution and amorphization of Ir and non-Ir metals in the catalysts during the OER. [9][10][11][12] Recently, it is reported that A x Ir y O z usually forms bulk with large size and irregular morphology due to the conventional use of solid phase synthesis method with high temperature and pressure. 13 Unlike the above catalysts, A x Ir y O z with regular morphology can expose more catalytic active sites.…”
Section: Introductionmentioning
confidence: 99%